Mathematical Problem-Solving Ability of Junior High School Students in Terms of Self-Efficacy - Fanisa Dina Amalia Dewi Umbara; Suhendra Suhendra; Yaya Sukjaya Kusumah (Universitas Swadaya Gunung Djati, 2022)
One of the essential mathematical abilities possessed by students is problem-solving ability. So that students can solve problems effectively, they need self-efficacy to help actualize and optimize their problem-solving ability. This research aims to describe the students' mathematical problem-solving ability based on self-efficacy differences. The method used in this research is qualitative with a phenomenological approach. The subjects were three students in grade VII at one of the junior high schools in Serang City, Banten. The indicator of problem-solving ability used in this research is related to students' success in solving various mathematical problems. The results of this research showed that student with high self-efficacy was able to solve closed mathematical problems inside and outside the mathematical context and open-ended mathematical problems outside the mathematical context. The student with moderate self-efficacy was able to solve closed mathematical problems inside mathematical context. The student with low self-efficacy was not able to solve all the mathematical problems given. Â Â